2023
DOI: 10.1002/admi.202202379
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Ultraviolet Photodetector Based on an AlGaN/GaN HEMT with Graphene‐On‐p‐GaN Mesa Structure

Abstract: The advantageous role of 2D electron gas presence at the AlGaN/GaN interface attracts huge interest in the field of GaN‐based ultraviolet photodetector technology. However, the presence of high dark current deteriorates the photodetector performance by diminishing several figures of merit. In this work, enhanced figures of merit are demonstrated by employing interdigitated p‐GaN finger structure on the top of the AlGaN/GaN heterostructure. The commonly present high dark current in p‐GaN/AlGaN/GaN planar photod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 62 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Recently, two-dimensional (2D) transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention as next-generation semiconductors due to their fascinating electrical and optical properties. The electrical properties of 2D TMD-based field effect transistors can be effectively and nondestructively tuned by coating various organic molecules on their surface due to surface charge-transfer doping or formation of heterostructures. However, many previous reports found that this may result in an increase of both ON and OFF current, severely limiting the signal-to-noise ratio (SNR) when applied to photosensing applications (i.e., phototransistors). An example of such an increase in OFF current after coating organic molecules on a 2D TMD-based transistor is shown in Figure S1. Therefore, the effective application of organic coatings on TMD-based phototransistors dictates that it is necessary to limit potential OFF current increases and act as a light absorption layer to improve the photosensitivity (i.e., SNR) of TMD-based phototransistors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two-dimensional (2D) transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention as next-generation semiconductors due to their fascinating electrical and optical properties. The electrical properties of 2D TMD-based field effect transistors can be effectively and nondestructively tuned by coating various organic molecules on their surface due to surface charge-transfer doping or formation of heterostructures. However, many previous reports found that this may result in an increase of both ON and OFF current, severely limiting the signal-to-noise ratio (SNR) when applied to photosensing applications (i.e., phototransistors). An example of such an increase in OFF current after coating organic molecules on a 2D TMD-based transistor is shown in Figure S1. Therefore, the effective application of organic coatings on TMD-based phototransistors dictates that it is necessary to limit potential OFF current increases and act as a light absorption layer to improve the photosensitivity (i.e., SNR) of TMD-based phototransistors.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of single-band detectors, broadband photodetectors such as UV-visible, visible-infrared, and UV-visible-infrared photodetectors are preferred in order to meet the ever-increasing multifunctional requirements. The formation of heterojunction between two materials is advantageous in terms of the suppression of photocarrier recombination and can benefit from different materials’ properties, thus resulting in excellent stability, fast response/recovery time, high responsivity, and enhanced external quantum efficiency [ 9 , 10 , 11 , 12 ]. Wide-bandgap metal oxides such as TiO 2 , NiO, WO 3 , Ga 2 O 3 , ZnO, InO, In 2 O 3 , SnO 2 , and their heterostructures with existing semiconductors are also promising for such a wide range of photodetection and sensing application [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%